2021
DOI: 10.19105/panyonara.v3i2.5140
|View full text |Cite
|
Sign up to set email alerts
|

Indonesian EFL Students’ Perceptions on Learning Autonomy in Online Learning Delivery Mode

Abstract: The online learning delivery method is increasingly used in the teaching and learning process at universities. This type of learning is relatively new to students, in particular to Indonesian EFL students. Students' learning autonomy in an online learning system is inevitably required. Autonomy in online learning and in offline learning can be differently perceived by the students. This study aimed at revealing EFL students' perception on learning autonomy in an online learning method. A questionnaire was used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…For instance, the results showed that most students see online learning as independent learning in which they must be aware of and motivated to learn on their own, responsible for their learning, and self-directed and governed in their learning. They also thought that autonomous online learning could help them learn how to solve problems, think critically, and take the initiative to learn (Dalilan, 2021). Basically, several ways can evolve students' independent learning, namely Self-Directed Learning (SDL).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the results showed that most students see online learning as independent learning in which they must be aware of and motivated to learn on their own, responsible for their learning, and self-directed and governed in their learning. They also thought that autonomous online learning could help them learn how to solve problems, think critically, and take the initiative to learn (Dalilan, 2021). Basically, several ways can evolve students' independent learning, namely Self-Directed Learning (SDL).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have investigated the attitudes of EFL teachers toward LA implementation in their teaching (Almusharraf, 2020;Lengkanawati, 2017;Ningsih & Yusuf, 2020;Yuzulia, 2020;Yuzulia & Yusuf, 2019), as well as the perspectives from students (Boonma & Swatevacharkul, 2020;Dalilan, 2021;Tuan, 2021). Lengkanawati (2017) found that the majority of the teachers participating in her study were eager to bring LA principles into teachinglearning practices, regardless of the challenges in its implementation.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on LA have been widely explored (Almusharraf, 2020;Boonma & Swatevacharkul, 2020;Dalilan, 2021;Lengkanawati, 2017;Ningsih & Yusuf, 2020;Tuan, 2021;Yuzulia, 2020;Yuzulia & Yusuf, 2019). However, there has been only…”
Section: Introductionmentioning
confidence: 99%
“…There were five previous studies pertaining to the major theme of this present library study. The first study was conducted by Dalilan (2021) who discovered that the majority of Indonesian university EFL learners were capable of elevating their learning autonomy characters after being supported by meaning-making and contextual learning dynamics. Istiqomah (2020) uncovered that a vast majority of Indonesian university EFL learners were skilled at comprehending various listening contents autonomously since their lecturers addressed a wide variety of authentic listening materials.…”
Section: Introductionmentioning
confidence: 99%